Nursing care in postwar Madrid - Elena Chamorro Rebollo; José Siles González; Cristina Díaz Pérez; Oscar álvarez López
Objective.To describe the work of the Salus Infirmorum Sisterhood in caring for the most underprivileged individuals from the postwar outskirts of Madrid, through the voluntary service of the nurses who were part of that Institution. Methods. A historical study based on the analysis of primary sources from the Sisterhood's archives. Results. Salus Infirmorum once relied on more than 100 volunteer nurses who treated over 425-thousand people in 21 parish dispensaries located within the neediest neighborhoods of Madrid, providing both preventative and curative medical care. Nurses were offered adequate training in exchange for the care provided. Conclusion. Salus Infirmorum took healthcare to the streets of Madrid, treating patients in improvised medical clinics set up in parishes or in the patient's own home, as the situation required, in addition to training women who otherwise would not have had access to it.